(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
This study looked into the hydrogen production from phenol steam reforming over Zirconia (ZrO2)-supported nickel-cobalt catalysts diluted with silicon carbide (SiC). The objective of this study is to obtain the effect of catalyst dilution on hydrogen production and the phenol conversion in various SiC dilutions. The catalysts were prepared by impregnation method and their performance tests were carried out in a micro fixed bed reactor at atmospheric pressure and 800 Â°C temperature, feed flow rate 0.36 mL/min, weight of catalyst 0.2 g, and dilution range of 0.05 to 0.35 g (1:0 to 1:1.75). The results showed that the catalyst dilution does not affect much on the catalyst activity toward phenol conversion. However, it does improve the conversion of phenol with the presence of SiC. The maximum conversion was at 0.3 g (1:1.5) SiC dilution, which was of 98.9 % and 0.6 mole fraction of hydrogen.Â